Can inequality be tamed through boundary work? A qualitative study of health promotion aimed at reducing health inequalities. (July 2017) - Pedersen, Pia Vivian; Hjelmar, Ulf; Høybye, Mette Terp; Rod, Morten Hulvej
Abstract: This paper examines the organisational dynamics that arise in health promotion aimed at reducing health inequalities. The paper draws on ethnographic fieldwork among public health officers in Danish municipalities and qualitative interviews from an evaluation of health promotion programmes targeting homeless and other marginalised citizens. Analytically, we focus on 'boundary work', i.e. the ways in which social and symbolic boundaries are established, maintained, transgressed and negotiated, both at the administrative level and among frontline professionals. The paper discusses three types of boundary work: (i) demarcating professional domains; (ii) setting the boundaries of the task itself; and (iii) managing administrative boundaries. The main argument is that the production, maintenance and transgression of these three types of boundaries constitute central and time-consuming aspects of the practices of public health professionals, and that boundary work constitutes an important element in professional practices seeking to 'tame a wicked problem', such as social inequalities in health. A cross-cutting feature of the three types of boundary work is the management of the divide between health and social issues, which the professionals seemingly seek to uphold and transgress at the same time. The paper thus contributes to ongoing discussions of intersectoral action to address health inequalities. Furthermore, it extends the scope and application of the concept of boundary work in the sociology of public health by suggesting that the focus in previous research on professional demarcation be broadened in order to capture other types of boundaries that shape, and are shaped by, professional practices. Highlights: Analysis of practices of professionals engaged in reducing health inequalities. Taming health inequalities requires time-consuming boundary work. Three types of boundary work are presented and discussed. Professional and administrative boundaries are both maintained and transgressed. Setting the boundaries of the task means redefining the inequality problem itself.